Assessing the Influence of mineralogy and texture on the ore breakage characteristics of drill core and crushed ore using the JKRBT - Hill, Herbert Hill (Department of Chemical Engineering, 2021)
Textural variability is a key component in addressing process challenges resulting from variability in the ore being mined. Textural variability arises from differences in the types of mineral grains present, their relative abundance and the type of interactions they have with one another. Increased textural variability is the largest contributor to mineral processing challenges in terms of mill throughput and flotation concentrate grades. Processing of ores with high textural variability often results in reduced throughput and the recovery of lower grade product, if low-grade material is not eliminated prior to arriving at the concentrator. Geometallurgy provides a powerful tool to manage ore variability better by using geological and metallurgical information during plant design and operation. The geometallurgical approach contributes towards minimising and controlling operational and technical risk of ore variability. Ore breakage characterisation is a pivotal part of geometallurgy which aims to quantify the relationship between the energy supplied for breakage and the size of the resultant progeny. The Julius Kruttschnitt Rotary Breakage Tester® (JKRBT) is an ore breakage characterisation device designed as a geometallurgical tool which can use both crushed ore and drill core samples. Drill core is especially important as it the material used for geometallurgical testing during exploration and resource definition. The JKRBT is more accurate and the test work is less time consuming than its predecessors. However, sample availability is a major concern when performing metallurgical testing as numerous tests need to be performed to get a complete view of the metallurgical response of the given ore type. This means that very little of the sample is available for ore breakage characterisation. The aim of this work is to understand the relationship between mineral texture and the ore breakage characteristics of several samples for both drill core and crushed ore which are the two sample types used at exploration and operational levels. The work is aimed at addressing the problem of sample availability in geometallurgical testing by developing an ore breakage characterisation test protocol that uses minimal sample to extract relative hardness indices. To assess the influence of mineral texture on the ore breakage characteristics, five different ore types were used. The ore was prepared by coring different size drill core and crushing using a jaw crusher. The samples were subjected to controlled single impact breakage tests using the JKRBT. A standard test consisted of 3 energy levels (low, medium and high) tested on 3-4 particle size fractions (small, medium, large and very large). The least particle protocol was developed using an ore which was considered to be fine-grained and homogenous. In developing the protocol, all the steps of the standard procedure were followed except the number of particles per test was progressively reduced from 30 particles to a threshold of 5 particles. From ore breakage characterization tests performed, it was observed that ore S was the most resistant to breakage while ore P was the least resistant to breakage. Ore A was found to be more competent than ore B and ore C but less competent that ore P. The differences in the ore breakage characteristics were attributed to the grain size distribution of the dominant constituent minerals for each sample. The findings were attributed to an increase in the surface area available for contact due to the decrease in grain size which results in less stress per unit area and thus more resistance to breakage. The hardness of an ore can be considered to be a function of the mineral hardness and its relative abundance. Using the relative mineral abundance and Mohs hardness scale, it was concluded that the more abundant the harder minerals in an ore, the more resistant to breakage the ore is. Drill core particles consistently produced a coarser progeny than crushed particles at the same conditions. The observed trend was attributed to differences in the particle shape between the crushed particles (angular) and drill core particles (cylindrical). Angular particles have a larger surface area exposed for energy absorption and therefore break more easily than drill cores. Chapter 5 showed that the proposed abridged ore breakage characterisation test that uses the minimal number of particles to extract ore breakage indices can be applied for both homogenous and heterogenous ore types. The results also show that the proposed least particles protocol can be used for ore breakage characterisation tests using both crushed ore and drill core particles. The number of particles can be reduced to as little as 10 particles per test while still obtaining the same ore breakage indices as those obtained from the standard procedure. The abridged protocol will be especially useful in situations where the amount of ore available for metallurgical testing is limited.